Principal’s Managerial Competencies and Utilization of Financial Resource in Public Secondary School Rivers state, Nigeria. - Damiete Gibson , Amachree (International Journal of Educational Management, 2025)
The study investigated principal managerial competencies and utilisation of f inancial resources in public secondary schools in Rivers State. Three research questions and three null hypotheses were formulated to guide the study. The design of the study was a correlational design with a population of 286 principal in all the secondary schools present in the 23 local government areas. The sample of the study comprised of 166 principals which represented 58.04% of the population. This was done using the stratified random sampling technique. The instrument for data collection was a self-designed questionnaire, captioned "Principal Managerial Competencies and Utilization of Financial Resources Questionnaire (PMCUFR9), with a reliability coefficient of 0.88 and also, the Financial Resources Questionnaire (FRO) had a reliability coefficient of 0.74. In analyzing the data, mean score and standard deviation will be used to answer the research questions, while the Pearson Product Moment Correlation Coefficient, using the SPSS version 25. The study discovered that to a high extent principal possess asset management competence, which includes skills in negotiation and project management, strong time management skills, highly skilled in math and finance, confident and assertive on my d ecision concerning school finance, establish procedures to manage the utilization of funds. Hence it was concluded that principal must demonstrate the needed level of competencies and this recommended that The principal should advance skills f inancial report by demonstrating high level proficiency in excel, detail oriented and highly organized, ensure faithful accountability of financial report, communicate r elevant financial needs to stakeholders and ensure that financial report and documentation is within timeline.